Persistent Organic Pollutants in Mediterranean Seawater and Processes Affecting Their Accumulation in Plankton - Berrojalbiz, Naiara; Dachs, Jordi; Del Vento, Sabino; Ojeda, María José; Valle, María Carmen; Castro-Jiménez, Javier; Mariani, Giulio; Wollgast, Jan; Hanke, Georg (Environmental science & technology, 2011)
The Mediterranean and Black Seas are unique marine environments subject to important anthropogenic pressures due to riverine and atmospheric inputs of organic pollutants. Here, we report the results obtained during two east–west sampling cruises in June 2006 and May 2007 from Barcelona to Istanbul and Alexandria, respectively, where water and plankton samples were collected simultaneously. Both matrixes were analyzed for hexaclorochyclohexanes (HCHs), hexachlorobenzene (HCB), and 41 polychlorinated biphenyl (PCB) congeners. The comparison of the measured HCB and HCHs concentrations with previously reported dissolved phase concentrations suggests a temporal decline in their concentrations since the 1990s. On the contrary, PCB seawater concentrations did not exhibit such a decline, but show a significant spatial variability in dissolved concentrations with lower levels in the open Western and South Eastern Mediterranean, and higher concentrations in the Black, Marmara, and Aegean Seas and Sicilian Strait. PCB and OCPs (organochlorine pesticides) concentrations in plankton were higher at lower plankton biomass, but the intensity of this trend depended on the compound hydrophobicity (K OW). For the more persistent PCBs and HCB, the observed dependence of POP concentrations in plankton versus biomass can be explained by interactions between air–water exchange, particle settling, and/or bioaccumulation processes, whereas degradation processes occurring in the photic zone drive the trends shown by the more labile HCHs. The results presented here provide clear evidence of the important physical and biogeochemical controls on POP occurrence in the marine environment.